Approaching Carbon Nanotube Reinforcing Limit in B4C Matrix Composites Produced by Chemical Vapor Infiltration1. Issue 2 (23rd September 2013) - Li, Kaiyuan; Yang, Yingchao; Gu, Zhanjun; Howe, Jane Y.; Eres, Gyula; Zhang, Litong; Li, Xiaodong; Pan, Zhengwei
<x xml:space="preserve">Abstract</x> Toughening ceramics has been a long‐standing challenge. By chemically infiltrating B4C into aligned carbon nanotubes (CNTs) sheets, we fabricate a novel CNT/B4C composite with a fracture strength approaching the theoretical maximum of B4C matrix. The CNT/B4C composites simultaneously possess a strongly bonded tube/matrix interface and an amorphous, crack‐free B4C matrix. The fracture strength of the CNT/B4C nanowires is about 1–2 orders of magnitude higher than that of the bulk B4C. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>